Reproducible and Repeatable Generation of 4-He, γ-rays, and Heat in Light and Heavy Waters at Room Temperature - Torabi-Monfared, Hossein; Doroodmand, Mohammad Mahdi (Frontiers in Energy Research, 2022)
The extraordinary claim of observing nuclear fusion products and excess heat during heavy water electrolysis at room temperature was sensationalized in 1989. Unfortunately, it was rejected quickly by scientific communities. At the last attempt to access the accuracy of the previous works in this field, a Google-funded team tried to examine all reported works with their corresponding conditions to confirm the claimed results. Finally, they found that there was no reasonable proof of nuclear fusion reactions under the reported conditions. Here, we introduced a method to apply a unique triggering potential waveform to a simple two micro-shaft system in both heavy and light concentrated salinity waters which resulted in detecting 4-helium, gamma rays, and heat repeatedly and reproducibly. In this work, two types of nuclear fusion reactions were observed: 1) A D + D fusion reaction in potassium halide salt solutions in heavy water and 2) a new type of fusion reaction in carbon-containing salt solutions in both light and heavy waters. In the latter type, it was proved that the existence of carbon atoms in an anion structure is critical to observe the 4-helium, gamma rays, and heat.